The Effectiveness of STEAM-Based Augmented Reality in Improving Students' Science Literacy Skills - Asyri, Derin; Asyri, Devan (JKTP: Jurnal Kajian Teknologi Pendidikan, 2024)
This study aims to describe the effectiveness of Augmented Reality STEAM-Based Learning on Students' Science Literacy. Achievement. This Quasi-Experimental study uses a posttest-only control group design. This study was conducted on students. The sample was taken using a random sampling technique from the intake class, which consists of three parallel classes. Then, students from classes A and B were treated as experimental groups, and control groups were classes C and D. Students in the experimental group were taught using AR-assisted STEAM-based learning, while in the control group, students were taught by applying conventional learning methods. In data collection, this study used a science achievement test and a science literacy test. The results showed that the application of Augmented Reality-assisted STEAM-based learning was quite effective in improving students' science literacy, the application of Augmented Reality-assisted STEAM-based learning was effective in improving students' learning achievement, there were differences in science literacy results and student learning achievement between students who were taught using Augmented Reality-assisted STEAM-based learning and students who were taught by implementing conventional learning. Abstrak Penelitian ini bertujuan untuk mendeskripsikan efektivitas Augmented Reality STEAM-Based Learning terhadap Literasi Sains Mahasiswa. Pencapaian. Penelitian Quasi-Experimental ini menggunakan desain posttest-only control group design. Penelitian ini dilakukan pada Mahasiswa. Sampel diambil menggunakan teknik random sampling dari kelas intake, yang terdiri dari tiga kelas paralel. Kemudian, mahasiswa dari kelas A dan B diperlakukan sebagai kelompok eksperimen, dan kelompok kontrol kelas C dan D. Mahasiswa kelompok eksperimen diajarkan menggunakan pembelajaran berbasis STEAM berbantuan AR, sedangkan kelompok kontrol, mahasiswa diajarkan dengan menerapkan metode pembelajaran konvensional. Dalam pengumpulan data, penelitian ini menggunakan tes prestasi sains dan tes literasi sains. Hasil penelitian menunjukkan bahwa penerapan pembelajaran berbasis STEAM berbantuan Augmented Reality cukup efektif dalam meningkatkan literasi sains mahasiswa, penerapan pembelajaran berbasis STEAM berbantuan Augmented Reality efektif dalam meningkatkan prestasi belajar mahasiswa, ada perbedaan hasil literasi sains dan prestasi belajar mahasiswa antara mahasiiswa yang dibelajarkan dengan menggunakan pembelajaran berbasis STEAM berbantuan Augmented Reality dengan mahasiswa yang dibelajarkan dengan menerapkan pembelajaran konvensional.